The Influence of Sales Growth, Corporate Governance and Company Characteristics on Tax Avoidance - Al-Hanief, Albastha Azmil Qahhar; Putra, Yananto Mihadi (Inisiatif Masyarakat Jurnal Indonesia (IMAJI), 2024)
This study aims to determine the influence of Sales Growth, Corporate Governance, and Company Characteristics on Tax Avoidance in industrial sector companies listed on the Indonesia Stock Exchange in 2020-2022. The sample was determined using the Purposive Sampling method. The method used in this study is a descriptive method with a quantitative approach and the analysis technique used is a classical assumption test. The analysis of the influence of variable x on y in this study produced the following results; Sales growth has no effect on tax avoidance, the audit committee has no effect on tax avoidance, the independent board of commissioners has no effect on tax avoidance, leverage has an effect on tax avoidance and profitability has an impact on tax avoidance.